2010
DOI: 10.1152/ajpendo.00703.2009
|View full text |Cite
|
Sign up to set email alerts
|

Changes in skeletal muscle mitochondria in response to the development of type 2 diabetes or prevention by daily wheel running in hyperphagic OLETF rats

Abstract: The temporal changes in skeletal muscle mitochondrial content and lipid metabolism that precede type 2 diabetes are largely unknown. Here we examined skeletal muscle mitochondrial fatty acid oxidation (MitoFAOX) and markers of mitochondrial gene expression and protein content in sedentary 20-and 40-wk-old hyperphagic, obese Otsuka Long-Evans Tokushima fatty (OLETF-SED) rats. Changes in OLETF-SED rats were compared with two groups of rats who maintained insulin sensitivity: age-matched OLETF rats given access t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
40
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 36 publications
6
40
2
Order By: Relevance
“…These animals are selectively bred with a mutated and functionally inoperative cholecystokinin-1 receptor (34, 35), which results in hyperphagia and the progressive development of obesity, insulin resistance, type 2 diabetes, and NAFLD (43). We have demonstrated previously that these pathological metabolic events are prevented in physically active OLETF rats given daily access to voluntary running wheels (41,42,45,46). …”
mentioning
confidence: 89%
“…These animals are selectively bred with a mutated and functionally inoperative cholecystokinin-1 receptor (34, 35), which results in hyperphagia and the progressive development of obesity, insulin resistance, type 2 diabetes, and NAFLD (43). We have demonstrated previously that these pathological metabolic events are prevented in physically active OLETF rats given daily access to voluntary running wheels (41,42,45,46). …”
mentioning
confidence: 89%
“…Running volumes can vary from ϳ1 up to 20 km over a 12-h dark cycle period but are typically consistent within experiments. In addition, the mitochondrial adaptations in skeletal muscle after VWR (29,39) are usually very modest and pale in comparison to what is measured in rats forced to run on treadmills (11). Therefore, it could be argued that VWR in rats is analogous to higher daily ambulatory activity in humans, while treadmill running in rats would mimic programmed endurance exercise in humans.…”
Section: Wheel Lock Studies In Rodentsmentioning
confidence: 99%
“…Both high-fat diets and hyperphagic-dietary overconsumption induce insulin resistance in sedentary rodent models; however, if the rodents in these studies are allowed to obtain physical activity (VWR, treadmill running, or swimming), insulin resistance does not develop. For example, we have shown that providing VWR to Otsuka Long Evans Tokushima Fatty rats (OLETF; hyperphagic-obese model prone to T2D) out to 40 wk of age prevents insulin resistance and the development of T2D unequivocally (39). This protection occurs even though the running OLETF have a large decrease in running distance by 40 wk of age (ϳ4 km/day by 40 wk of age down from ϳ11-12 km/day at 12 wk of age).…”
Section: Response To Inactivity: Preservation or Pathologymentioning
confidence: 99%
“…In fact, significant hepatic TAG accumulation occurred in as little as 4 -5 wk postweaning in the sedentary, hyperphagic OLETF rats (witnessed at 8 wk of age) (44). In a series of studies, we have demonstrated that these pathological metabolic events are prevented when the OLETFs (4) are given daily access to voluntary running wheels and allowed to be physically active (42,43,45,46). However, it is unclear how long these pathological events can be prevented after becoming inactive.…”
mentioning
confidence: 99%